Brothers in arms: platelets and neutrophils in ischemic stroke. Issue 5 (September 2021) - Denorme, Frederik; Rustad, John L.; Campbell, Robert A.
Abstract : Purpose of review: In this review, we will describe how the combined ability of platelets and neutrophils to interact with each other drives ischemic stroke brain injury. Recent findings: Neutrophils are one of the first cells to respond during ischemic stroke. Although animals stroke models have indicated targeting neutrophils improves outcomes, clinical trials have failed to yield successful strategies. Platelets play a critical role in recruiting neutrophils to sites of injury by acting as a bridge to the injured endothelium. After initial platelet adhesion, neutrophils can rapidly bind platelets through P-selectin and glycoprotein Ibα. In addition, recent data implicated platelet phosphatidylserine as a novel key regulator of platelet-neutrophil interactions in the setting of ischemic stroke. Inhibition of procoagulant platelets decreases circulating platelet-neutrophil aggregates and thereby reduces infarct size. Platelet binding alters neutrophil function, which contributes to the injury associated with ischemic stroke. This includes inducing the release of neutrophil extracellular traps, which are neurotoxic and pro-thrombotic, leading to impaired stroke outcomes. Summary: Platelet-neutrophil interactions significantly contribute to the pathophysiology of ischemic stroke brain injury. Better understanding the mechanisms behind their formation and the downstream consequences of their interactions will lead to improved therapies for stroke patients.